Trans-scale influence of molecular states and intermolecular interactions on self-diffusion - Arampour, Meysam E.; Jin, Hanhui; Fan, Jianren (International journal of heat and mass transfer, 2025)
Understanding self-diffusion in fluids is critical for advancing material transport theories and optimizing engineering applications. This study employs Molecular Dynamics (MD) simulations to investigate how molecular-scale interactions (σ, ϵ) and molecular energy states (EK,EP) influence self-diffusion. Building on these insights, a novel mathematical model is developed, incorporating these parameters, and validated against experimental data, achieving superior predictive accuracy over existing models with Average Absolute Deviation (AAD = 0.7%). The findings provide a quantitative framework linking molecular interactions to macroscopic transport phenomena, offering deeper insights into self-diffusion in nano-engineering applications. •Trans-scale effects of molecular interactions and energy states on self-diffusion are explored.•Roles of mean free path, kinetic energy, and interaction intensity in self-diffusion revealed.•Molecular-scale-based model shows significant advantage over existing self-diffusion models.